EVALUASI KONSUMEN TERHADAP ATRIBUT PRODUK BAURAN PEMASARAN JAMUR TIRAM PUSAT BUDIDAYA JAMUR RIAU (PUSDAMURI) - Novrianto '; Fajar Restuhadi; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to identify and analyze attributes of oyster mushroom product. And to analyze the importance and performance of mix product attribute of oyster mushroom marketing. The experiment was conducted in Business Center Unit of Riau Mushroom Cultivation (Unit Usaha Pusat Budidaya Jamur Riau (Pusdamuri). Questionnaires were conducted in a place that became the location Pusdamuri oyster mushrooms marketing. The method that used to determine the respondents is non-probability sampling. Then continued with convenience sampling. The result showed that the results of Importance of Performance Analisys there are three attributes in Quadrant I (top priority). The attribute is the price, packaging design and availability. In Quadrant II, (feat maintain) there are six attributes, first taste, second nutritional value, benefit, color, location, and last advertising and promotion. Attributes that are in Quadrant III (low priority) are the shelf life, the content (volume) of packaging and packaging labels. In Quadrant IV (redundant) there are two attributes, namely size and customer service. Based on Customer Statisfaction Index (CSI), CSI is known that the value of 70.67% in the range of 66% - 80.99% which means that the respondent has satisfied the performance conducted by Pusdamuri (Centre for Mushroom Cultivation Riau). Consumers activities in purchase of oyster mushrooms can be used as input for producers and retailers to adjust to the demand (conformance to requirment). Keywords: product attributes, Importance Performance Analisys,CSI